A retroperitoneal urinoma secondary to metastatic urothelial carcinoma mimicking psoas muscle malignancy: Case Report and literature review - Li, Tianping; Lv, Haijuan (Frontiers in Oncology, 2026)
PurposeThis study aims to improve the understanding of imaging features of urinoma associated with urothelial carcinoma metastasis, enhance preoperative diagnostic accuracy, and reduce misdiagnosis rates.MethodsA 71-year-old male was admitted for evaluation following the incidental imaging detection of a left ureteral mass during an outpatient visit over the preceding 10 days. The patient was asymptomatic. Physical examination revealed a blood pressure of 195/88 mmHg, with no tenderness in either renal region. Laboratory investigations showed normal urinalysis and urinary cytology, with no tumor cells observed in urine smears. Contrast-enhanced CT urography (CTU) was subsequently performed.ResultsContrast-enhanced CT revealed a large cystic-solid mass in the left retroperitoneal and psoas muscle region, with poorly defined margins relative to the left kidney. The left ureter traversed the lesion and exhibited enhancement within the solid components, raising suspicion for a low-grade malignant tumor originating from the psoas muscle and involving the left kidney and ureter. Surgical pathology confirmed an invasive high-grade urothelial carcinoma of the left ureter, with infiltration into retroperitoneal cysts, the adjacent kidney, and the psoas muscle. Six months postoperatively, the tumor recurred and progressed rapidly, with evidence of widespread metastatic spread.ConclusionCTU plays a crucial role in diagnosing urothelial tumors, though its accuracy may be limited in patients with kidney dysfunction. The characteristic course of the ureter traversing a mass, along with hyper enhancing solid components at the obstructed distal ureter and adjacent tissues, can assist in accurate diagnosis and help reduce the risk of misdiagnosis. However, surgery for locally invasive tumors risks spreading cancer cells and worsening outcomes.